Band Alignment of Atomic Layer Deposited SiO2 and Al2O3 on (AlxGa1-x)2O3 for x = 0.2-0.65. (1st January 2019) - Fares, Chaker; Kneiß, Max; von Wenckstern, Holger; Tadjer, Marko; Ren, Fan; Lambers, Eric; Grundmann, Marius; Pearton, S. J.
Abstract : (Alx Ga1-x )2 O3 is attracting attention for use in heterostructure devices grown on Ga2 O3 substrates. The band alignments of amorphous, atomic layer deposited Al2 O3 and SiO2 on (Alx Ga1-x )2 O3 for x = 0.2-0.65 have been determined using high resolution X-ray photoelectron spectroscopy. The (Alx Ga1-x )2 O3 was grown by continuous composition spread Pulsed Laser Deposition (CCS-PLD). The band alignments are type I (nested gap) in all cases, with conduction band offsets ranging from 1.57-0.67 eV for Al2 O3 on (Al0.2 Ga0.8 )2 O3 to (Al0.65 Ga0.35 )2 O3 and 2.35-1.40 eV for SiO2 on these same compositions. Correspondingly, the valence band offsets are all >1.25 eV for SiO2 and 0.23-0.33eV for Al2 O3 over this composition range. While these are the first reports for Al2 O3 on (Alx Ga1-x )2 O3 over such a wide composition range, our results differ by up to 0.4 eV in conduction band offsets from past studies of SiO2 on (Alx Ga1-x )2 O3 of a more limited composition range, which themselves have shown variations of up to 0.5eV for conduction band offsets on nominally the same composition. These differences emphasize the influence of experimental conditions in determining band alignments.